The Development and Effectiveness Evaluation of Game Labs in Learning: Content Analysis and the Impact of Gamification - Januar Singgih Abdullah; Agus Juhana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study examines the development and effectiveness evaluation of game labs in learning through a Systematic Literature Review (SLR) approach. Game labs, or laboratories that incorporate gamification elements, offer an innovative solution to create interactive and safe learning experiences. The urgency of this research is based on the need for more adaptive education to enhance student engagement and understanding, especially in practical learning that requires a high level of safety. The purpose of this study is to identify development trends, included content, and the effectiveness of game labs in supporting student motivation and understanding across various disciplines, such as biology, chemistry, mechanical engineering, and cybersecurity. The results show that game labs using gamification elements like challenges, 3D visualization, and rewards can significantly increase student engagement and understanding. Game labs also allow students to explore in a controlled environment, fostering motivation and independent learning. In conclusion, game labs are effective in enriching the learning experience and are relevant for widespread implementation to meet the needs of more innovative and interactive learning.